(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This article deals with the topic of onomatopoeia – a stylistic devices that allows to illustrate the content of texts on the sonic level, thanks to which they can easily move the imagination of especially young recipients. It is this feature that makes onomatopoeic effect so often used in children’s songs. The aim of the article is to characterize the onomatopoeias found in poems for children by Julian Tuwim and their translation into German. Using fragments of selected works, the author will indicate what linguistic devices are used to create the onomatopoeic effect in Tuwim’s poems, as well as what types of onomatopoeia are present in them. In addition, this issue will be presented in terms of translation – the author will answer the questions of whether and to what extent the onomatopoeic features of the poems in question were preserved in the translation into German and what solutions the translator used to deal with the difficulties.